A Review of Main Eye Movement Tracking Methods. Issue 4 (March 2021) - Li, Zhaowei; Guo, Peiyuan; Song, Chen
Abstract: The study of eye movement has been last for centuries. Over the past decade, scientists have developed many new eye-tracking methods. During that same period, technological innovations have made eye-tracking units more affordable. The article provides a systematic review on some main eye-tracking methods. This paper also includes the factors that may influence the eye-gaze tracking and the application of gaze estimation in many areas. In this article, we provide information on eye tracking in hopes of improving the quality and reporting of eye-tracking research in communication.